Sistem Informasi Manajemen dan reservasi Online (SI-RO) Pada Unit Bisnis PT. Gama Multi Yogyakarta - Dyajeng Aulia Sakinah; Wina Yusnaeni; Hasan Basri (IMTechno: Journal of Industrial Management and Technology, 2023)
Developments in the existing tourism sector D.I Yogyakarta is periodically growing rapidly. The number of tourists who come from various regions makes the people of Yogyakarta Special Region provide various attractions offered, ranging from culinary tours, natural attractions, cultural tours and others, as an attraction that is in demand by tourists traveling. During this time homestay and guesthouse managed by Gama Multi still apply manual method in the process of booking, service, and reporting that is with microsoft excel. So the use of computers in homestay and guest house operations is less than optimal because it is not supported by a computerized system. The need for a computerized system that can improve the online service system so that it can provide ease of management and reservation with data stored neatly and easily searchable. Information system built using a qualitative descriptive method for data collection and waterfall method software development. The application is built in the form of a receptionist website making it easier for the receptionist to manage orders to check-in guests, service transactions, and up to checkout guests. Admin website application to facilitate the Gama accommodation in managing lodging data and does not need to make a manual report because the report is programmed (automatically).